Potassium Profile in Heart Failure Patients Before and After Hospitalization at Prof. Dr. I.G.N.G. Ngoerah Hospital - Kadek Indra Aryani; Ni Putu Ika Swastiartha; Ni Komang Ayu Krisma Suriatha Putri; Ni Kadek Mas Ari Pratiwi; Made Suta Wahyudi; Rini Noviyani (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Hypokalemia in patients with heart failure is increasing, with an increasing incidence of 6.8% in Asia and 19.7% in Indonesia; globally, 63 million people suffer from heart failure. Hypokalemia is defined as a serum potassium level below 3.5 mEq/L [mmol/L], which can lead to decreased heart function, muscle weakness, arrhythmias and cardiac arrest. The use of diuretic drugs such as furosemide in heart failure patients may be a risk factor for hypokalemia. Objective: This study aims to determine the difference in potassium levels before and after furosemide administration as well as the possibility of hypokalemia due to furosemide administration in inpatients diagnosed with heart failure at Prof. Dr. I.G.N.G. Ngoerah Hospital. Methods: This is a cross-sectional observational study with retrospective medical record collection. The minimum sample size was calculated using Lemeshow's Formula of One Proportion Estimation Method with Absolute Precision Proportion, data normality test with Kolmogorov-Smirnov (p>0.05) and parametric test with paired t-test (p<0.05). This study included 101 patients that met the inclusion criteria with 11 patients having more than one inpatient visit, so a total 114 'patients' medical records were obtained. Results: Potassium levels before and after hospitalization showed a significant difference (p<0.05). A total of 84 'patients' data showed a decrease in potassium levels, with 49 of them showing a reduction in >15% and 35 showing a decrease of ≤15%. Conclusion: Prevalence of hypokalemia in patients with a diagnosis of heart failure and furosemide therapy at Prof. Dr. I.G.N.G. Ngoerah Hospital during January 2022-December 2023 after hospitalization was 29%.